Auditoría en seguridad vial de la abscisa km 7+000 a km 13+000. tramo, sector Cerritos – la Virginia – Cauyá, Troncal de Occidente ruta 25. Código 2507 (2021)
The work carried out on carrying out a Road Safety Audit. from Km 7 + 000 to Km 13 + 000, Cerritos - La Virginia - Cauyá, to the variables: barriers, geometric design and signaling, to establish the physical condition of the road and its effects on the road actors that circulate along it , a thoroughness was carried out, complying with the development of the objective by means of the descriptive quantitative methodology, for this the variables used for each objective were identified, the methods and tools used were presented, the results found were described, of which it was highlighted that in some sectors maintenance is lacking